Preference vs. Authority: A Comparison of Student Searching in a Subject-Specific Indexing and Abstracting Database and a Customized Discovery Layer - Dahlen, Sarah; Hanson, Kathlene (College & research libraries, 2017)
Discovery layers provide a simplified interface for searching library resources. Libraries with limited finances make decisions about retaining indexing and abstracting databases when similar information is available in discovery layers. These decisions should be informed by student success at finding quality information as well as satisfaction with search interfaces. Students executed searches in two discovery layer configurations and an indexing and abstracting database. While students reported a preference for discovery layers, the articles selected from the indexing and abstracting database were more authoritative. These results illuminate the relative strengths of these tools, informing decisions about resource allocation and discovery configuration.